Sphingosine kinase 1 and cancer: a systematic review and meta-analysis. - Yun Zhang; Yan Wang; Zhi Wan; Shiping Liu; Yu Cao; Zhi Zeng (PLoS ONE)
Background Sphingosine kinase 1 (SK1) is a key regulator of the dynamic ceramide/sphingosine 1-phosphate rheostat balance and important in the pathological cancer genesis, progression, and metastasis processes. Many studies have demonstrated SK1 overexpressed in various cancers, but no meta-analysis has evaluated the relationship between SK1 and various cancers. Methods We retrieved relevant articles from the PubMed, EBSCO, ISI, and OVID databases. A pooled odds ratio (OR) was used to assess the associations between SK1 expression and cancer; hazard ratios (HR) were used for 5-year and overall survival. Review Manager 5.0 was used for the meta-analysis, and publication bias was evaluated with STATA 12.0 (Egger's test). Results Thirty-four eligible studies (n=4,673 patients) were identified. SK1 positivity and high expression were significantly different between cancer, non-cancer, and benign tissues. SK1 mRNA and protein expression levels were elevated in the cancer tissues, compared with the normal tissues. SK1 positivity rates differed between various cancer types (lowest [27.3%] in estrogen receptor-positive breast cancer and highest [82.2%] in tongue squamous cell carcinoma). SK1 positivity and high expression were associated with 5-year survival; the HR was 1.86 (95% confidence interval [CI], 1.18-2.94) for breast cancer, 1.58 (1.08-2.31) for gastric cancer, and 2.68 (2.10-3.44) for other cancers; the total cancer HR was 2.21 (95% CI, 1.83-2.67; P < 0.00001). The overall survival HRs were 2.09 (95% CI, 1.35-3.22), 1.56 (1.08-2.25), and 2.62 (2.05-3.35) in breast, gastric, and other cancers, respectively. The total effect HR was 2.21 (95% CI, 1.83-2.66; P < 0.00001). Conclusions SK1 positivity and high expression were significantly associated with cancer and a shorter 5-year and overall survival. SK1 positivity rates vary tremendously among the cancer types. It is necessary to further explore whether SK1 might be a predictive biomarker of outcomes in cancer patients.